2010
DOI: 10.3945/ajcn.2009.28521
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to colonic fermentation of nondigestible carbohydrates of a previous evening meal increase tissue glucose uptake and moderate glucose-associated inflammation

Abstract: In healthy subjects, factors related to colonic fermentation of nondigestible carbohydrates increase peripheral insulin sensitivity and moderate glucose-associated inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 48 publications
(54 reference statements)
7
70
1
Order By: Relevance
“…62,63 These changes can persist for hours as was demonstrated in men who ate a fiber rich evening meal and exhibited morning serum butyrate levels comparatively higher compared with those who ate a meal relatively low in fiber. 64 These findings indicate that the concentrations of serum SCFAs are dynamic and fluctuate in response to dietary fiber manipulation. …”
Section: Microbial Scfa Production and Systemic Traffickingmentioning
confidence: 89%
“…62,63 These changes can persist for hours as was demonstrated in men who ate a fiber rich evening meal and exhibited morning serum butyrate levels comparatively higher compared with those who ate a meal relatively low in fiber. 64 These findings indicate that the concentrations of serum SCFAs are dynamic and fluctuate in response to dietary fiber manipulation. …”
Section: Microbial Scfa Production and Systemic Traffickingmentioning
confidence: 89%
“…Although there is good observational evidence for whole grains reducing the risk of type 2 diabetes, there is only limited information on the effect of whole grains on glucose metabolism kinetics and insulin response. In a single meal study, whole-grain barley improved peripheral insulin sensitivity as indicated by an increased rate of glucose disappearance (46) . Recent work supports the present hypothesis that whole grains reduce peripheral insulin resistance compared with refined grains (39) , even though no effects on body composition were found in the 8-week study.…”
Section: Branched-chain Amino Acids Aromatic Amino Acids Acyl-carnimentioning
confidence: 99%
“…barley kernels) reduces plasma glucose levels by nearly 29% in the morning, increases tissue uptake of glucose by 30% and associated with a lower post-prandial circulating IL-6 and TNF-α level. [7] Diabetes is also associated with an increased expression of markers of oxidative stress. For instance patients with diabetes tend to have higher levels of lipid peroxidation than non-diabetics.…”
Section: Diabetes Mellitus and Oxidative Stress In The Gastrointestinalmentioning
confidence: 99%